Coefficient Inequality For Perturbed Harmonic Mappings - Çağlar, Mert; Yavuz Duman, Emel; POLATOĞLU, YAŞAR (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, England, 2010)
The aim of this work is to give the coefficient inequality for the perturbed harmonic mappings in the open unit disc D. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Harmonic mapping; Coefficient inequality; harmonik haritalama; katsayı eşitsizliği